EMPLOYEE PERFORMANCE BASED ON LEADERSHIP STYLE, JOB PROMOTION AND WORK ENVIRONMENT - Khayatun, Siti; Hartarini, Yovita Mumpuni; Ariyanti, Lisa (JURNAL STIE SEMARANG, 2024)
This study aims to determine the direct or indirect effects of performance issues in a service company, namely "Toha Okky Heru & Rekan Public Appraisal Services Office," with work motivation, job satisfaction, and organizational commitment as intervening variables to demonstrate their impact on employees performance.The research employed a quantitative approach, with data collected using an online questionnaire distributed to a sample of 111 respondents. The Likert scale with a range of 1 to 10 was used, and the data were analyzed using Structural Equation Modeling (SEM) with Partial Least Square (PLS). The instruments underwent tests for validity and reliability, multicollinearity, and R-Square (goodness of fit) evaluation.The results showed that Leadership Style does not have a positive effect on Employee Performance, with an original sample value of 0.175 and at statistical value less than the t table (0.872 < 1.982), indicating that Leadership Style has no significant effect on performance. Job Promotion was proven to have a positive effect on Employee Performance, with an original sample value of 0.495 and at statistical value greater than the t table (2.740 > 1.982), indicating that Job Promotion has a significant impact on employee performance. However, the Work Environment was also found not to have a significant effect on Employee Performance, with an original sample value of 0.146 and at statistical value less than the t table (0.938 < 1.982).Based on the research results, leadership style does not have a significant impact on employee performance at KJPP Toha, Okky, Heru & Rekan. This suggests that leadership that does not actively engage with employees or communicate effectively does not significantly affect job performance. In contrast, job promotion has a positive and significant influence on employee performance. Employees who receive promotions feel appreciated and motivated to work better, thereby improving their overall performance. Furthermore, the work environment does not have a significant impact on employee performance, indicating that once the work environment is adequate, further improvements in the work environment will not greatly affect performance.